2010
DOI: 10.3324/haematol.2010.032680
|View full text |Cite
|
Sign up to set email alerts
|

The topoisomerase II inhibitor voreloxin causes cell cycle arrest and apoptosis in myeloid leukemia cells and acts in synergy with cytarabine

Abstract: BackgroundTopoisomerase II is essential for the maintenance of DNA integrity and the survival of proliferating cells. Topoisomerase II poisons, including etoposide and doxorubicin, inhibit enzymemediated DNA ligation causing the accumulation of double-stranded breaks and have been front-line drugs for the treatment of leukemia for many years. Voreloxin is a first-in-class anticancer quinolone derivative that intercalates DNA and inhibits topoisomerase II. The efficacy and mechanisms of action of voreloxin in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
49
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 45 publications
(45 reference statements)
0
49
0
Order By: Relevance
“…10 Importantly, due to the stability of the quinolone backbone, vosaroxin does not produce significant free radicals, 11 or the reactive oxygen species implicated in the cumulative cardiotoxicity seen with anthracyclines. 10 Additionally, vosaroxin is not a substrate for the P glycoprotein efflux pump, and its activity is independent of p53 family members; [11][12][13] it may, therefore, bypass some mechanisms of chemotherapy resistance. Consistent with this, single-agent activity has been noted in anthracycline-resistant populations, 13 including women whose ovarian cancer progressed on liposomal doxorubicin 14 and AML patients with refractory/relapsed disease.…”
Section: Introductionmentioning
confidence: 99%
“…10 Importantly, due to the stability of the quinolone backbone, vosaroxin does not produce significant free radicals, 11 or the reactive oxygen species implicated in the cumulative cardiotoxicity seen with anthracyclines. 10 Additionally, vosaroxin is not a substrate for the P glycoprotein efflux pump, and its activity is independent of p53 family members; [11][12][13] it may, therefore, bypass some mechanisms of chemotherapy resistance. Consistent with this, single-agent activity has been noted in anthracycline-resistant populations, 13 including women whose ovarian cancer progressed on liposomal doxorubicin 14 and AML patients with refractory/relapsed disease.…”
Section: Introductionmentioning
confidence: 99%
“…Administration of a single intravenous (i.v.) dose of vosaroxin was shown to result in activation of caspase-3, a key mediator of apoptosis and its activity is independent of p53 [48]. The long tumor half-life observed (8 h) in non-clinical investigation [50] also supported an intermittent dosing schedule.…”
Section: Drug Evaluationmentioning
confidence: 85%
“…Preclinical studies have demonstrated effective synergy when vosaroxin was combined with cytarabine (Ara-C) [48,51]. Authors suggested this enhanced cytotoxicity is likely the result of cells exiting S phase with cytarabine-induced DNA damage and entering G2 phase, unable to repair these DNA DSB and sustaining further insult as a result of the action of vosaroxin.…”
Section: Drug Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…Vosaroxin is a naphthyridine analog (Figure 1), structurally related to quinolone antibacterials, that exerts its anticancer activity exclusively by DNA intercalation and inhibition of topoisomerase II, leading to site-selective DNA double-strand breaks and apoptosis [26][27][28]. Vosaroxin is not a substrate for P-glycoprotein drug pumps, and can induce apoptosis independent of p53, thereby avoiding two common mechanisms of drug resistance [29].…”
Section: Research Papermentioning
confidence: 99%